Comorbidities as an indication for metabolic surgery - Schwarz, Anne-Catherine; Billeter, Adrian; Scheurlen, Katharina; Blüher, Matthias; Müller, Beat P. (Visceral medicine, 2018)
Metabolic diseases, comprising type 2 diabetes mellitus (T2DM), dyslipidemia, and non-alcoholic steatohepatitis (NASH), are rapidly increasing worldwide. Conservative medical therapy, including the newly available drugs, has only limited effects and does neither influence survival or the development of micro- or macrovascular complications, nor the progression of NASH to liver cirrhosis, nor the development of hepatocellular carcinomas in the NASH liver. In contrast, metabolic surgery is very effective independent of the preoperative body mass index (BMI) in reducing overall and cardiovascular mortality in patients with T2DM. Furthermore, metabolic surgery significantly reduces the development of micro- and macrovascular complications while being the most effective therapy in order to achieve remission of T2DM and to reach the targeted glycemic control. Importantly, even existing diabetic complications such as nephropathy as well as the features of NASH can be reversed by metabolic surgery. Here, we propose indications for metabolic surgery due to T2DM and NASH based on a simple but objective, disease-specific staging system. We outline the use of the Edmonton Obesity Staging System (EOSS) as a clinical staging system independent of the BMI that will identify patients who will benefit the most from metabolic surgery.
Gesehen am 03.09.2019